ARAH PENGEMBANGAN SISTEM KEPEGAWAIAN PERGURUAN TINGGI BADAN HUKUM PENDIDIKAN (PT BHP) - Machmud, Senen (Majalah Bisnis & IPTEK, 2021)
Changes in the status of the University of the State-owned legal entity (BHMN) into Legal Education (BHP) in accordance with the mandate of Law No. 9 of 2009, the logical consequence is how the Higher Education system management personnel in accordance with the framework of Legal Education, especially related to recruitment, development, remuneration, and labor separation. College management strategies in the future are influenced by changes in environmental conditions requires the leadership to develop programs that are able to translate current issues and to support future business plans. Alignment between the business and planning of human resources (HR) can build a business plan that ultimately determine the human resource needs. Human resources development system is directed to design an efficient, effective, and accountable, including recruitment, development, compensation, and labor separation. Keywords: employment system; human resources planning